2021
DOI: 10.3390/s21103532
|View full text |Cite
|
Sign up to set email alerts
|

Field-Portable Microplastic Sensing in Aqueous Environments: A Perspective on Emerging Techniques

Abstract: Microplastics (MPs) have been found in aqueous environments ranging from rural ponds and lakes to the deep ocean. Despite the ubiquity of MPs, our ability to characterize MPs in the environment is limited by the lack of technologies for rapidly and accurately identifying and quantifying MPs. Although standards exist for MP sample collection and preparation, methods of MP analysis vary considerably and produce data with a broad range of data content and quality. The need for extensive analysis-specific sample p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 109 publications
(136 reference statements)
0
9
0
Order By: Relevance
“…Despite commercially available water quality sensors, which offer capabilities to detect a select set of physicochemical and biological parameters, like conductivity/salinity, dissolved oxygen, pH, turbidity, chlorophyll, and temperature, to the best of our knowledge, there is not any proven in situ and real-time sensor technology to detect and characterize nanoplastic particles in water. Recent advances in employing underwater spectral imaging and evolving image processing have improved the quality of underwater object detection in different turbid waters. This laboratory has also demonstrated that detecting materials in turbid water is still feasible using nano-DIHM with a minimum light penetration . In situ flow-through sensors that can provide real-time physicochemical data on the quantity and characteristics of nano/microplastics in water, like the AI-assisted nano-DIHM developed in this work, can be used to develop scalable monitoring systems for different aquatic ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…Despite commercially available water quality sensors, which offer capabilities to detect a select set of physicochemical and biological parameters, like conductivity/salinity, dissolved oxygen, pH, turbidity, chlorophyll, and temperature, to the best of our knowledge, there is not any proven in situ and real-time sensor technology to detect and characterize nanoplastic particles in water. Recent advances in employing underwater spectral imaging and evolving image processing have improved the quality of underwater object detection in different turbid waters. This laboratory has also demonstrated that detecting materials in turbid water is still feasible using nano-DIHM with a minimum light penetration . In situ flow-through sensors that can provide real-time physicochemical data on the quantity and characteristics of nano/microplastics in water, like the AI-assisted nano-DIHM developed in this work, can be used to develop scalable monitoring systems for different aquatic ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in order to distinguish between the effects of particle size and type, experiments are simultaneously conducted at both low and high frequencies. 92,93 There is a way to tell the difference between PE MPs (212-1000 mm) and interferences of the same size (for example, organisms and seeds) in tap water (with an average ow rate of 103 ± 8 mL min −1 ) by looking at how the impedance changes at 1.1 MHz and 10 kHz. It is evident that the location of the particles and the corresponding impedance change allow for the differentiation of PE MPs, seeds, and living creatures in tap water.…”
Section: Impedance Spectroscopymentioning
confidence: 99%
“…Even though these techniques can provide accurate material characterization, they are regarded as expensive, non-portable, and time-consuming for microparticle analysis. [6,7] On the other hand, there are high-throughput techniques which provide the geometric size of microparticles-but not their material characteristics-such as resistive pulse sensing [8] (commonly used in Coulter counters and nanopore analyzers) and more generally impedance cytometry. [9] By augmenting impedance cytometry with the capability of material characterization, the applications mentioned above can be streamlined significantly.…”
Section: Introductionmentioning
confidence: 99%